"Optoelectronics, Vol.2: Intermediate Study: A Self-Teaching, Text, Including; Radiometrics, Color CRTS, Projects" - Martin (Vaughn D) ("43/19, Aziz mulk, 1st st, 2nd floor1000 lights, Anna salaiChennai,Tamilnadu,India-6,044 52142483/38builders_line@sify.com", 1997)
adiometrics ; Color ; CRTS
22.5
Keywords: adiometrics ; Color ; CRTS